Wood anatomy of six species of the genus Cecropia Loefl. (Urticaceae) - Reis, Pamella Carolline Marques dos; Reis, Alisson Rodrigo Souza; Lisboa, Pedro Luiz Braga; Reis, Leonardo Pequeno (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The objective of this work was to anatomically characterize six species of Cecropia to contribute to the identification of the following species: C. distachya Huber, C. latiloba Miq., C. obtusa Trécul, C. obtusifolia Bertol., C. palmata Willd. and C. sciadophylla Mart. The anatomic descriptions followed the traditional methodologies used for studies of wood anatomy. The species showed multiseriate and heterogeneous rays, composed of procumbent cells, square and erect, an aliform parenchyma with variation of wings (with losangular extension, linear and thick), predominantly solitary pores and diffuse porosity. C. latiloba Miq. was the only specie that had diffuse axial channels and septate fibers, being the specie with the greatest variation among the six species analysed. At macroscopic level, the species differentiated by the growth layers and the type of axial parenchyma, and, at microscopic level, the differentiation occurred by the presence or absence of septate fibers, axial channels and type of axial parenchyma. Even without an optic tool the species can be differentiated.